The global burden of cataracts and its attributable risk factors in 204 countries and territories: a systematic analysis of the global burden of disease study - Wang, Dongyue; Tang, Tong; Li, Peiheng; Zhao, Jing; Shen, Bairong; Zhang, Ming (Frontiers in Public Health, 2024)
The global distribution and trends in the attributable burden of cataract risk have rarely been systematically explored. To guide the development of targeted and accurate cataract screening and treatment strategies, we analyzed the burden of cataract disease attributable to known risk factors.This study utilized detailed cataract data from the Global Burden of Disease e 2019, and we analyzed disability-adjusted life years (DALYs) e each risk factor from 1990 to 2019. Additionally, we calculated estimated annual percentage changes (EAPCs) during the study period. The results revealed that from 1990-2019, the global age-standardized DALYs of e attributable to particulate matter pollution, smoking, high fasting glucose plasma and high BMI showed steady downward trends (1990-2009: